Identification of Aquifer, Ground Water-Bearing Rock, using Vertical Electrical Sounding (VES): East Lampung Case Study - Intan Andriani Putri; Risky Martin Antosia; Alhada Farduwin; Reza Rizki; Yudha Styawan; Sillak Hasiany (Penerbit Kemala Indonesia, 2023)
A one-dimensional geo-electrical method using Vertical Electrical Sounding (VES) has been carried out to model lithology and identify an aquifer, a water-bearing rock, in East Lampung to provide the water needs of the poultry breeding industry (PT. X) that is going to be established in the near future. Two VES points had been surveyed using Schlumberger electrode configuration to achieve good depth penetration and good vertical resolution. Geophysical modeling is not unique, overcoming this issue could be done using a global inversion method. A global inversion technique called Particle Swarm Optimization (PSO) was performed to create more reliable subsurface lithology, resulting in around 5 – 11% errors. The PSO algorithm deployed here took 1.000 particle numbers with ω=0.8; αl=1.8; and αg=2. The result shows that the study area’s lithology consists of Tuff, Sandy Tuffaceous, and Shaley Tuff. Sandy Tuffaceous is identified as a confining aquifer zone. There are two potential aquifer zones, Aquifer I and Aquifer II. Aquifer II has more potential as water resources of the industry due to its thickness, moreover, it is topped by impermeable Shaley tuff that prevents local climate effects such as rain that could decrease water quality.